Entrance to the Museum of Fine Arts, ca. 1876-1909 - Unknown (Tufts Archival Research Center, 2005)
Street-level view of the main entrance to the Museum of Fine Arts, located on St. James Avenue at Copley Square between Dartmouth Street to the southwest and Trinity Place to the northeast. A statue is located between the two main doors, which face north-northwest towards St. James Avenue and Copley Square. 9 1/8 x 7 1/8 Photographs